{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

Lecture 11

# Lecture 11 - Combining Reactions to Calculate H N2 O2 2NO...

This preview shows pages 1–3. Sign up to view the full content.

Combining Reactions to Calculate H H(kJ) N 2 + O 2 →2NO 180 2NO + O 2 → 2NO 2 -112 Adding: N 2 + 2O 2 → 2NO 2 68 When two reactions add up to make a third combined reaction, we can also add the H for each reaction to calculate the H for the combined reaction. This is known as Hess’s Law, and is a consequence of the more fundamental Law of Conservation of Energy. H (kJ) C(graphite) + O 2 → CO 2 (g) -394 C(diamond) + O 2 → CO 2 (g) -396 Calculate H for C(graphite) → C(diamond) Combine the above reactions by first reversing the diamond combustion. H(kJ) CO 2 (g) → C(diamond) + O 2 +396 C(graphite) + O 2 → CO 2 -394 Adding: C(graphite) → C(diamond) +2 The above calculation indicates that there is very little energy difference between graphite and diamond. Does this mean that we can take 12.0 g (1 mol) of graphite, add a measly 2.0 kJ, (roughly equivalent to increasing the temperature of a cup of water by 2 degrees C) and instantly get 12.0 g diamond? Obviously not. Why not? H is a state function, and the difference of 2 kJ between diamond and graphite accurately represents the overall enthalpy difference between final and initial states. But H does not predict how easy the process is to accomplish or how fast the reaction will occur. This particular process (graphite diamond), involves breaking down the strong bonds of graphite (lots of energy needed) and then reforming them as diamond (lots of energy released--all but 2 kJ of the energy required to break the graphite bonds). This process is difficult and expensive. The small value of H tells us nothing about the ease of actually accomplishing the change. H compares initial and final states, not the process of the change. The study of kinetics (chapter 12 of our text) looks at the factors that affect reaction rate as well as the mechanism and process of how chemical reactions occur.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Given the following data: H(kJ) 2B + 2 3 O 2 → B 2 O 3 -1273 B 2 H 6 + 3O 2 → B 2 O 3 + 3H 2 O(g) -2035 H 2 + ½ O 2 → H 2 O( ) -286 H 2 O( ) → H 2 O(g) 44 Calculate H for 2B + 3H 2 → B 2 H 6 H(kJ) B 2 O 3 + 3H 2 O(g) → B 2 H 6 + 3O 2 +2035 Flip 2 nd equation
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

### Page1 / 10

Lecture 11 - Combining Reactions to Calculate H N2 O2 2NO...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online